Effect of betaine, vitamin C and vitamin E on egg quality, hatchability, and markers of liver and renal functions in dual-purpose breeding hens exposed to chronic heat stress - Attia, Y. A.; Abd El-Hamid, A. E.; Abdallah, A. A.; Berikaa, M. A.; El-Gandy, M. F.; Şahin, Kazım; Abou-Shehema, B. M. (Eugen Ulmer Gmbh Co, 2018)
The objective of this study was to investigate the effects of betaine (Bet, 1000 mg/kg betaine), vitamin C (VC, 200 mg/kg ascorbic acid), and vitamin E (VE, 150 mg/kg DL-alpha-Tocopherol acetate) and their combinations on egg quality, hatchability and indices of liver and renal functions of dual-purpose breeding hens exposed to chronic heat stress. A total of 288 hens and 36 cocks from 32 to 48 weeks of age were divided into 9 treatment groups of 4 replicates each containing 8 hens and 1 cock. There were 9 experimental groups, one kept under thermoneutral condition and the others were kept under chronic heat stress (CHS). One of these 8 was used as a negative control and the other were supplemented with VC, VE and/or Bet and their combinations. Egg quality and fertility decreased in hens reared under heat stress without any supplementation during 32 to 48 weeks. Hens reared under heat stress and fed on a diet supplemented with either Bet, Vit C, Vit E or a combination of the supplements increased these parameters, hens supplemented with Vit C being greatest. Serum AST and ALT enzyme activities were greatest in hens reared under heat stress and fed on a diet with no supplementation, and were similar in all the other treatments. Although plasma Ca concentrations decreased in hens reared under heat stress and fed on a diet with no supplementation, plasma P concentrations and Ca/P ratios remained similar among treatments. Results of the present work demonstrated that supplementation of dual purpose breeder hens with vitamin C at 200 mg/kg diet or Bet at 1000 mg/kg is effective in alleviating the effects of chronic heat stress.
Einfluss von betain, vitamin C und vitamin E auf die eiqualität, den bruterfolg und ausgewählte indikatoren der leber- und nierenfunktion bei unter hitzestress gehaltenen legehennen des zweinutzungstyps
Keywords: Laying hen; dual purpose; parent stock; nutrition; betaine; vitamin C; vitamin E; heat stress; performance; hatching results; liver function